Impact of foreign currency derivatives on firm performance : evidence on Shari’ah and non-Shari’ah compliant firms - Zaminor Zamzamir@Zamzamin; Razali Haron; Zatul Karamah Ahmad Baharul Ulum; Anwar Hasan Abdullah Othman (Penerbit Universiti Kebangsaan Malaysia, 2022)
Hedging practices among Shari’ah compliant firms (ShC) are still not well explored and firms in Malaysia is very much lag behind in derivatives usage against firms in the developed countries. This study investigates the influence of financial derivatives usage on the value of Shari’ah and non-Shari’ah compliant firms (non-ShC) in Malaysia and compares the influence of derivatives usage on the value between the two categories of firms. To meet its objective, Generalized Method-of-Moment estimator (System-GMM) is employed on a set of panel data from 2000-2017. This study covers 200 firms engaged in derivatives which 59 firms are ShC firms and 141 are non-ShC firms. This study finds financial derivatives contribute positively to the value of Shari’ah compliant but negatively to the non-ShC firms. This study concludes that ShC performed better than its counterpart in risk management using derivatives. The findings enrich the current literature on the Islamic financial market and contribute to a better understanding relating to hedging activities. This study offers new evidence on risk management using derivatives in both Shari’ah and non- ShC firms and the importance of industrial diversification on firm value. This study suggests that the non-involvement in non-ShC firm’s activities contributes to the lower risk profile hence a more effective risk management of the Shari’ah compliant firms.